2019
DOI: 10.1007/s11442-019-1706-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on Tibet tourism based on tourism climate index

Abstract: Climate change is an important factor affecting the sustainable development of tourist destinations. Based on the monthly observation data of the main meteorological stations on the ground in Tibet from 1960 to 2015, this paper constructs a tourism climate index model. This index is used to quantitatively evaluate the tourism climate changes in Tibet, and investigate the impact of climate change on tourism. The results show that from 1960 to 2015, the temperature in Tibet increased by 1.35°C, and the tourism c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Studies in Europe and coastal areas have mainly focused on the sensitivity of the ecosystem and its response to climate change and pattern change over time [25][26][27][28][29][30], which measure ecosystem tolerance and vegetation response predictions to climate anomalies. In mainland areas, research on ecological vulnerability is more concentrated on land use patterns [31][32][33], desertification soil problems [24,[34][35][36], and human disturbances [37][38][39][40][41]. Typically, vulnerable zones with different topological characteristics are studied [38][39][40] to determine the determinants of vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Europe and coastal areas have mainly focused on the sensitivity of the ecosystem and its response to climate change and pattern change over time [25][26][27][28][29][30], which measure ecosystem tolerance and vegetation response predictions to climate anomalies. In mainland areas, research on ecological vulnerability is more concentrated on land use patterns [31][32][33], desertification soil problems [24,[34][35][36], and human disturbances [37][38][39][40][41]. Typically, vulnerable zones with different topological characteristics are studied [38][39][40] to determine the determinants of vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature comfort is an important part of current climate comfort research, and research on temperature comfort plays an important role in helping tourists select travel destinations and make travel decisions ( Perch-Nielsen et al, 2010 ). Tourism temperature comfort not only affects the length of the tourism comfort period and the choice of tourist destinations but also affects the tourism activities ways and the function of tourism resources ( Abed and Matzarakis, 2018 ; Zhong et al, 2019 ). Previous studies have found that temperature comfort is not only influenced by objective environmental factors, but the psychological adaption is also an important factor (such as knowledge, experience, and memory) is also an important factor in tourists’ temperature comfort ( Lu et al, 2016 ).…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, Mieczkowski developed the first index for the relationship between tourism and climate, the Tourism Climate Index (TCI), to assess the favorable and unfavorable climatic conditions according to the needs of visitors. Since its development, the TCI has been used extensively as a research tool for many regions and countries in the world, such as Europe [46][47][48], the Mediterranean [49], South Africa [50,51], Algeria [52], Australia [53], China [3,[54][55][56][57], Egypt [58], Georgia [59], Hungary [60], Iran [61][62][63][64][65], Turkey [66]. TCI merges seven climatic variables in five additive sub-indices.…”
Section: Progress With Tourism Climate Indicesmentioning
confidence: 99%
“…The Mediterranean region is the predominant factor for Europe's leading position in tourism with a growth higher than Western, Central Eastern, and Northern Europe [2]. The region, with a total 46,000 km coastline shared by 22 countries, welcomed more than 330 million international tourists in 2016, which is more than double the number recorded in 1995 [3]. Although beach tourism has provided the major offer in positioning such growth, urban tourism is an increasingly important element for the region.…”
Section: Introductionmentioning
confidence: 99%